Psychosocial Coping and Resilience of Pot Maker’s Children: Focus on Educational Challenges in Harotesa and Bobucho Primary Schools in Hadiya Zone-Hosana - Alemu, Roman (Technium Social Sciences Journal, 2020)
The purpose of this study was to assess coping and resilience of pot-makers’ children focus on educational challenges in Harotesa and Bobucho primary schools in Hadiya zone-Hosana town. The specific objectives were to see psychosocial coping strategies and resilience of pot makers’ children in the school, to identify educational challenges of pot makers’ children in the school and to compare educational achievement of pot makers’ children with the non- pot makers’ children. From 2112 population, the sample comprised 343 pot makers’ and non-pot makers’ children in Bobicho and Harotesa primary schools. The participants were chosen by Stratified, random sampling technique and the data was collected by using interview and questionnaire. The data obtained through questionnaire were analyzed using percentage, multi-nominal regression and chi-square. Chi-square test was used to find out the association between academic achievement and family background, the association between social interaction and family background and, association of coping and resilience by socio-demographic backgrounds of respondents. Multi-nominal regression was taken to see the magnitude and direction of the association i.e. to check whether the association is positive or negative. For qualitative part of the study, the analysis was made by transcription of the interpreting words directly obtained from the qualitative data. The finding indicates that some socio-economic and demographic backgrounds of respondents have significant relation with variables in relation to academic achievements and participation. From these, family background (pot makers’ and non- pot makers’) has significant association with academic achievement, condition of absent and active participation of respondents in the class at P<0.01. The multi-nominal regression result also shows that students’ low level of academic achievement is positively (directly) related with pot makers’ children (ß=1.76 and Wald =11.85) whereas none pot makers negatively associated with low academic achievement (ß=-0.25).In addition, the study has shown that copying and resilience strategies of discriminated children against harassments and segregations are variable. Accordingly, respondents’ strategy is significantly different among schools. For example, coping is positively associated with students who are learning in Bobicho (ß=3.1 and Wald 12.3). This implies using copying as a strategy is more common for students of Bobicho primary school than Harrotessa. On the basis of these results, it was suggested that, the schools should have a special treatment and monitoring for students of pottery workers family. Likewise, families and the nearby community shall contribute their part to reduce social discrimination in terms of preach equality, non-discrimination and fraternity. Moreover, the concerned bodies (such as families and schools should do their best to empower these groups thereby to increase their academic achievements and, pottery makers’ children (students) shall better use resilience than copying to challenge discrimination against them.